Monarch caterpillars are robust to combined exposure to the roadside micronutrients sodium and zinc. Issue 1 (9th August 2021) - Shephard, Alexander M; Mitchell, Timothy S; Snell-Rood, Emilie C
Abstract : Humans are increasing micronutrients in roadside habitats to levels that are potentially stressful for insect pollinators. We show that combined exposure to levels of sodium and zinc characteristic of high-traffic roadsides do not impact survival of developing monarch butterflies ( Danaus plexippus ), but sodium increases relative eye size and prolongs development. Abstract: Human activities are increasing the environmental availability of micronutrients, including sodium and some essential metals. Micronutrients are often limiting in animal diets but may have negative effects when consumed in excess. Though prior research has documented how elevated exposure to individual micronutrients can impact organismal development and fitness, we know less about combined effects of multiple micronutrients. In the wild, monarch butterfly larvae ( Danaus plexippus ) commonly consume plants in roadside habitats that contain elevated levels of sodium (from road salt) and zinc (from vehicle wear-and-tear). We reared monarch caterpillars to adulthood to test individual and combined effects of dietary sodium and zinc on components of fitness, sodium-linked phenotypes (proxies for neural and flight muscle development) and concentrations of sodium and zinc in adult butterflies. Monarch survival was not impacted by elevated sodium or zinc individually or in combination. Yet, monarchs feeding on sodium-treated milkweed developed relatively larger eyes, consistent with a positive effect of sodium on neural development. Measurements of element concentrations in butterfly and plant tissue indicated that monarchs had higher zinc levels than those present in zinc-treated milkweed but lower sodium levels than those present in sodium-treated milkweed. Monarchs developing on sodium-treated milkweed also had prolonged development time, which might be a cost associated with developing extra neural tissue or investing in mechanisms to excrete excess dietary sodium during the larval stage. Our results indicate that sodium, more than zinc, is likely influencing phenotypic development and performance of insect pollinators in roadside habitats. Yet, in contrast to previous work, our experiment suggests that the highest levels of sodium found along roads are not always harmful for developing monarchs. Future work could consider how potentially stressful effects of micronutrients could be mitigated by increased macronutrient availability or how developmental factors such as migratory status might increase micronutrient requirements.